Determination of Heavy and Trace Metals in Honey Using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) in South Eastern Zone of Tigray Region, Northern Ethiopia - Kusse Gudishe Goroya; Gebrewahd Abadi; Yoseph Alresauwm Asresahegn (Chemistry Department, The University of Brawijaya, 2021)
The present study aimed to determine concentration of heavy and trace metals (Fe, Cu, Mn, Zn, Co, Cd, Pb, As, and Hg) in honey by inductively coupled plasma optical emission spectrometry (ICP-OES). Samples passed through wet digestion methods following the optimum digestion condition by applying the reagents (30mL HNO3:30mL H2O2) at temperature of 270oc for 3 hours. The average concentrations of the metals are found in the range of 5.32-28.6 mg/kg for Fe, 0.24-0.749mg/kg for Cu, 0.627-4.401mg/kg Zn, 0.41-3.15mg/kg for Mn, 0.08-0.112 mg/kg for Co, 0.25-0.325mg/kg for Pb, 0.24-0.46mg/kg for As, ND-0.031mg/kg for Hg and 0.02-0.03mg/kg for Cd. This study shows that the honey in the studied area is a good sources of essential metals (Fe, Cu, Mn, Co and Zn) as they are found to be in the permissible limit. Moreover, the maximum concentration of the toxic metals determined in this work are below the level of toxicity as per the standard set by WHO/FAO.